LATAR BELAKANG PERNIKAHAN MAHASISWA DAN PENGARUHNYA TERHADAP PRESTASI AKADEMIK - Yusuf Nalim (Khazanah Pendidikan, 2013)
This study is based on reality in quite a number of students who have been married STAIN Pekalongan. The purpose of the study was to determine the factors underlying the marriage occurred among students STAIN Pekalongan and wanted to know if there is a difference between the academic achievement of students before and after marriage. Randomly selected sample of students who had been married STAIN. Method of data analysis is to use factor analysis and paired sample t test. The results showed, of 17 factors (variables) are proposed, elected to 12 significant factors underlying the decision to get married students. Furthermore the factors of 12 are four main factors (principal component) is formed as follows: (a) Religion and Mass Media with variables: eager to have offspring (children) (0.532), Worry be a spinster / exposed disgrace (0,529), unceasing information about sex from Mass Media (0.773), Effect of television shows (0.865), Effect of pornography (0.836), (b) interests in Business, with a variable: For the purpose of smooth business (0.969), to strengthen business networks (0.949), (c ) Economics and culture, with a variable: For the solution of economic problems (0.540), Effect of culture/ tradition (0,692), Ready to build lives of Household (-0.851), (d) Social, with variables: Fear happen adultery (0,700), Already work (0.755). Results of statistical analysis paired t test showed no significant difference between the academic achievement before she married after marriage. This is evident based on the t test produces p-value (probability value) of 0.761 (more than 0,05).